Media exposure and reproductive behaviour change among generations of adolescents in Ugep, Nigeria (2009)
This paper examines change in reproductive behaviour across several generations of adolescent girls in Ugep, sourtern Nigeria. It is based on a study of key factors promoting differences in girls' reproductive behaviour across this generations, which linked this change media exposure and a number of social variables that challenge traditional views of the relationships. The study found alterations in adolescent sexual activities, contraceptive prevalence, voluntary abortion and the fertility. Female age at sexual debut was found to be declining, with 11.3% of adolescent females initiating sex at 11 years relative to 4.1 percent from previous cohorts. This finding in particular reflects the onset of liberal sexual norms, accentuated by ease of entry into consensual unions and trends towards sexual networking. The general findings point to the role of western media, poverty and pressures related to an urbanizing lifestyle on girls' aspirations and reproductive choices. In this way,it contribute to the growing body of work on reproductive change in an era of serious population' debate and, therefore, suggests a need for adopting alternative models for explaining reproductive change in sub- saharan communities.